Challenges in Critical Care Medicine: An Overview of Puerto Rico’s Intensive Care Units - Egozcue-Dionisi, Mónica; Nieves-Nieves, José; Torrellas-Ruiz, Pedro A.; Fernández-González, Ricardo; Fernández-Medero, Rosángela L.; Adorno-Fontánez, José; Adorno-Fontánez, Edgardo; Rodríguez-Vega, Gloria (Puerto Rico Health Sciences Journal, 2013)
Objective: Puerto Rico (PR) has undergone rapid changes during the last decades. Some of these involve the health care system and the delivery of care to the critically ill patient. With this in mind, we investigated how the intensive care units throughout our island’s hospitals are organized so that we could establish a profile of the adult intensive care units (ICU) in PR. Methods: From January 1, 2010 through April 30, 2010, questionnaires were distributed by e-mail or fax to every hospital that maintained a critical care unit. The questionnaires asked for such details as the structure of the unit; whether is use on an open or closed model; the number of beds in the unit; the total number of faculty members in the unit; the credentials of the unit’s medical faculty and nursing staff; whether critical care service was available, and the different people in-charge of the unit during the day and at night. Results: A total of 33 questionnaires were distributed, of which 19 were collected and analyzed. Among the IC U directors who responded, the predominant specialty was cardiology. Surprisingly, only 26% of the hospitals had critical care specialists. In most of the institutions, an internist or a primary care physician was on site during the day, this individual directly supervised patients and had decision making authority. At night, however, patients were managed by supervising nurse with limited ability to medically identified patient complications , though primary care physician was always available by phone if a critical decision needed to be made. Some of the units used protocols as part of their medical management armamentarium. Conclusion: Although only a small percentage of the island’s IC Us participated in our project, the study’s findings serve as evidence of the need to re-evaluate the delivery of care to the critically ill population.